Linking Antimicrobial Resistance Surveillance Data to Provincial Hospital Records: A Descriptive Study of Patient and Facility-level Characteristics - Seungwon Lee; Paul E Ronksley; Stephanie Garies; Hude Quan; Peter Faris; Bing Li; Elizabeth Henderson (International Journal of Population Data Science, 2018)
Introduction Antimicrobial resistance (AMR) is an emerging phenomenon where microorganisms develop resistance against treatment antimicrobials, resulting in ineffective clinical interventions. The recent development of AMR surveillance systems at global and national stages highlights the growing importance of this topic from a public health perspective.